Government expenditure on Nigerian primary school education: benefit incidence approach (2002)
Human resources development is a key factor in economic development. Primary education represents the springboard for human resource development. Given the avoided pledge of government on public primary education, this study examined the benefit incidence of government expenditure on primary school education in Ibadan North Local Government Area of Oyo State, Nigeria. Data were collected with the aid of structured questionnaire administered on one hundred using systematic random sampling procedure. These data were analyzed using headcount (poverty) index and benefit incidence analysis. The result, of the study showed that on the basis of two-thirds of the mean per capita household expenditure ofN3307.00, about 24 percent of the respondents were core poor, 23 percent were moderately poor while the remaining 43 percent were non-poor. The enrolment share in public schools of these poverty groups was 26.9 percent for core poor, 32.9 percent for moderately poor and 40.2 percent for non-poor. Further, the results showed that average household spending on each child (N3, 428) was more than government unit subsidy at N1632. 78. The costs incurred by households were on transportation, feeding, purchase of books and stationeries, uniforms as well as non-tuition fees. It was revealed that households within the study area utilised public schools (94.0 percent) than private schools (6.0 percent). In conclusion, "on-poor households benefited more (40 percent) from government subsidy than the core poor households (27 percent).